Normality: A collection of essays. (April 2021) - Cryle, Peter; Stephens, Elizabeth
This article introduces a collection of articles written in response to a recently published intellectual and cultural history of normality by Peter Cryle and Elizabeth Stephens. It points to the fact that this special issue considerably extends and enriches the topical range of the book. The articles that follow discuss, in order, schooling in France at the time of the Revolution, phrenology in Europe and the US from 1840 to 1940, relations between commercial practice and scientific craniometry in 19th-century Britain and France, psychology in late 19th-century France, case studies in sexology and psychoanalysis in Central Europe, and biotypology in Southern Europe and Latin America.